The Correlation Between Students’ Comprehension of Reading and Their Vocabulary Mastery - Rahmawati, Yulis Dwi; Lindawati, Rini; Ganinda, Nurhayati (Philosophiamundi, 2024)
This research to find out the correlation between students’ comprehension of reading and their vocabulary mastery. This study uses correlational research. The population of this study were second-grade students of SMA Islam Brawijaya in the academic year 2023/2024. The sample consisted of 30 students. The main problem in this study was to determine whether there was a relationship between students' vocabulary mastery and their reading comprehension skills in learning English. The techniques used to obtain data are: first, collecting data from students' vocabulary tests and reading comprehension tests; second, calculating and classifying students' vocabulary mastery tests and students' reading comprehension; third, analyzing students' vocabulary scores and students' reading comprehension; finally, drawing conclusions based on the data. The results of the analysis show that there is a significant correlation between students' vocabulary mastery and their ability to understand a reading. This is proven because the average vocabulary mastery of students is 76.66, In the vocabulary table, the level of vocabulary mastery scores of students get a good score. Meanwhile, the score of students' reading comprehension is 84.66, In the table of scores of students' reading comprehension levels, students get a good score.